EvenUP: A case study of building cross-publisher collaboration on equity, diversity, inclusivity and belonging - Anthony Cond; Tasneem Bhopalwala; Valarie Guagnini (Insights: The UKSG Journal, 2023)
This case study charts the building of an informal collaboration in the scholarly publishing ecosystem to bring like-minded presses together to enhance Equity, Diversity, Inclusivity and Belonging (EDIB) practice. It is not intended to be a step-by-step guide on EDIB because excellent introductory resources for publishers already exist, nor is it a theoretically informed explication of collaborative advantage. Instead, it is a messy narrative of how university presses founded in 1534 through to 2022, with outputs ranging from more than 6,000 books a year to not having published a single book yet, could come together with openness to try and push forward a moral imperative. We share this experience, as a group of university press publishers, in case it helps others considering informal modes of collaboration to drive change.